A Study of Recent Mergers and Acquisitions in India and Their Impact on The Operating Performance and Shareholder Wealth - Pacheriwala, Rohit (2009)
This dissertation is a study on the objectives of mergers and acquisitions, as to why organisations undertake the inorganic mode of expansion. However the main focus is on studying the operating performance and shareholder value of acquiring companies and comparing their performance before and after the merger. To conduct a uniform research and arrive at an accurate conclusion, we restrict our research to only Indian companies. To get a broader perspective on India, we study 4 sectors namely aviation, banking, steel and oil and gas.